2019
DOI: 10.1007/s10571-019-00713-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Neuroinflammation and Neurotoxicity by Synthetic Hemozoin

Abstract: Hemozoin produced by Plasmodium falciparum during malaria infection has been linked to the neurological dysfunction in cerebral malaria. In this study, we determined whether a synthetic form of hemozoin (sHZ) produces neuroinflammation and neurotoxicity in cellular models. Incubation of BV-2 microglia with sHZ (200 and 400 µg/ml) induced significant elevation in the levels of TNFα, IL-6, IL-1β, NO/iNOS, phospho-p65, accompanied by an increase in DNA binding of NF-κB. Treatment of BV-2 microglia with sHZ increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Hemozoin is known to induce in ammation and morphological changes in microvascular endothelium (Medana and Turner 2006;Prato et al 2011), leading to an increase in blood brain barrier (BBB) permeability, neuroin ammation and neurological sequelae in survivors (Basilico et al 2003;Tripathi et al 2009). Similar to these reports, our investigations have revealed that a synthetic form of hemozoin is in fact able to induce neuroin ammation in BV-2 microglia (Velagapudi et al 2019). Consequently, reducing the CNS effects of hemozoin in CM is a potential adjunctive strategy in reducing the neurological outcomes of the disease.…”
Section: Introductionsupporting
confidence: 86%
“…Hemozoin is known to induce in ammation and morphological changes in microvascular endothelium (Medana and Turner 2006;Prato et al 2011), leading to an increase in blood brain barrier (BBB) permeability, neuroin ammation and neurological sequelae in survivors (Basilico et al 2003;Tripathi et al 2009). Similar to these reports, our investigations have revealed that a synthetic form of hemozoin is in fact able to induce neuroin ammation in BV-2 microglia (Velagapudi et al 2019). Consequently, reducing the CNS effects of hemozoin in CM is a potential adjunctive strategy in reducing the neurological outcomes of the disease.…”
Section: Introductionsupporting
confidence: 86%
“…The Caspase-Glo® 1 Inflammasome Assay (Promega) was used to measure the activity of caspase-1 directly in live cells or culture supernatants [ 30 ]. BV-2 microglia were seeded out in a 24-well plate at a density of 4 × 10 4 cells/ml and stimulated with S1 (10 ng/ml, 50 ng/ml and 10 ng/ml) for 24 h. After incubation, cell culture supernatants were collected and mixed with an equal volume of Caspase-Glo® 1 reagent or Caspase-Glo® 1 reagent + YVAD-CHO (1 µM) in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…The caspase-Glo ® 1 inflammasome assay (Promega) was used to measure the activity of caspase-1 directly in live cells or culture supernatants [30]. BV-2 microglia were seeded out in 24-well plate at a density of 4 × 10 4 cells/mL and stimulated with S1 glycoprotein (10, 50 and 10 ng/mL) for 24 h. After incubation, cell culture supernatants were collected and mixed with equal volume of Caspase-Glo ® 1 reagent or Caspase-Glo ® 1 reagent + YVAD-CHO (1 μM) in a 96-well plate.…”
Section: Caspase-glo ® 1 Inflammasome Assaymentioning
confidence: 99%